SPATIAL AND LANDSCAPE CHANGES IN THE HOUSING DEVELOPMENT OF GDAŃSK SUBURBAN VILLAGES - Poczobut, Joanna (Quaestiones Geographicae, 2020)
In the article the specificity of development of Gdańsk suburban villages is considered. The data from recent years concerning demographic changes in communes will be analysed. The analysis of four selected villages will show the settlement changes and contemporary non-rural types of buildings. Spatial processes, which in terms of an extensive rural economy have already led to the change and depreciation of qualities of their current order and landscape, will be described.